Metalorganic chemical vapor deposition-regrown Ga-rich InGaP films on SiGe virtual substrates for Si-based III-V optoelectronic device applications - Kim, TaeWan (2017)
Ga-rich InGaP materials are attractive applications for yellow-green spectral range optoelectronics such as light-emitting diodes and solar cells on silicon substrate. Bulk, Ga-rich InGaP films grown by metalorganic chemical vapor deposition on SiGe virtual substrates were investigated in the V/III compositional ratio range of 44.3–402 using chamber pressures from 100 to 200 mbar. These films were nominally lattice matched to the SiGe virtual substrate with a bandgap energy of 2.07–2.09 eV at low temperature (10 K). The authors show that the surface morphology of the Ga-rich InGaP films was dependent on the growth conditions, including the V/III gas phase ratio, pressure, and growth rate. By optimizing the growth conditions, the authors achieved improved surface morphologies of the Ga-rich InGaP films. The hillock density of the films produced using a V/III gas phase ratio of 44.3 and 75.4, a growth pressure of 100 mbar, and a growth rate of 0.9 μm/h was about an order of magnitude lower (30.3–50 × 104 cm−2) than that observed using higher V/III gas phase ratios such as 201 and 402. An increase in luminescence efficiency of Ga-rich InGaP materials was observed when the hillock density is lower. The authors discuss the mechanisms of the hillock formation.